Impact of Syncope on Quality of Life: Validation of a Measure in Patients Undergoing Tilt Testing - Nave-Leal, E (2015)
INTRODUCTION AND OBJECTIVES: Recurrent syncope has a significant impact on quality of life. The development of measurement scales to assess this impact that are easy to use in clinical settings is crucial. The objective of the present study is a preliminary validation of the Impact of Syncope on Quality of Life questionnaire for the Portuguese population. METHODS: The instrument underwent a process of translation, validation, analysis of cultural appropriateness and cognitive debriefing. A population of 39 patients with a history of recurrent syncope (>1 year) who underwent tilt testing, aged 52.1 ± 16.4 years (21-83), 43.5% male, most in active employment (n=18) or retired (n=13), constituted a convenience sample. The resulting Portuguese version is similar to the original, with 12 items in a single aggregate score, and underwent statistical validation, with assessment of reliability, validity and stability over time. RESULTS: With regard to reliability, the internal consistency of the scale is 0.9. Assessment of convergent and discriminant validity showed statistically significant results (p<0.01). Regarding stability over time, a test-retest of this instrument at six months after tilt testing with 22 patients of the sample who had not undergone any clinical intervention found no statistically significant changes in quality of life. CONCLUSIONS: The results indicate that this instrument is of value for assessing quality of life in patients with recurrent syncope in Portugal.